2018
DOI: 10.1016/j.isci.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Perovskite Solar Cell to High-Energy Particle Irradiations in Space Environment

Abstract: In the originally published version of this article, due to an oversight during the proofing process, the values in column ''Cell 2'' of Table 1 were incorrectly reported, with an additional number to the left of the percentage number. The article has now been corrected online. The journal apologizes for the error and any confusion it may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…[16][17][18] Beyond conventional terrestrial implementation, [19][20][21] perovskite solar cells have recently found their potential applications for near-space and polar-region use in other extreme conditions. [22][23][24] Spacecraft often use high efficiency single-crystal Si or III-V semiconductor solar cells as the source of power generation. Photovoltaic devices for space applications have strict requirements, including high PCE with high specific power and specific volume, tolerance of space radiation damage, and stable performance through thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Beyond conventional terrestrial implementation, [19][20][21] perovskite solar cells have recently found their potential applications for near-space and polar-region use in other extreme conditions. [22][23][24] Spacecraft often use high efficiency single-crystal Si or III-V semiconductor solar cells as the source of power generation. Photovoltaic devices for space applications have strict requirements, including high PCE with high specific power and specific volume, tolerance of space radiation damage, and stable performance through thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
“…26 Also, originating from the ionic nature of perovskites, these cells have shown improved tolerance against high-energy proton or electron irradiation as compared to conventional photovoltaics. 22,[27][28][29][30] Moreover, the low temperature application of photovoltaic…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several reports show the decomposition of MAPbI3 to PbI2 after even soft X-ray exposure 39 . On the other hand radiation tolerance 26 or even radiation enhanced behaviour is also frequently reported for HHPs. 27 This remarkable radiation resistance is referred to the "self-healing" i.e.…”
Section: Figure 2: Gammavoltaic Effect Of Mapbi3 Exposed To the γ Radmentioning
confidence: 94%
“…Another attractive characteristic of perovskites is their tolerance to ionizing radiation. Tests done at Caltech [51] and elsewhere [52], [53] have shown that while perovskites suffer some displacement damage in high radiation fields, the damage can be annealed out to return the device to its undamaged operating state. This eliminates the need for cover glass, greatly reducing the mass of the cells.…”
Section: Architecture Comparisonsmentioning
confidence: 99%